2018
DOI: 10.6007/ijarbss/v8-i5/4225
|View full text |Cite
|
Sign up to set email alerts
|

Penang Muslims’ Perception on Factors Influencing Intention to Give Cash Waqf

Abstract: Cash waqf started in Penang since 1994 by offering various schemes that could attract the Muslim community in Penang to participate in cash waqf giving. However, the opposite occurs when the amount of cash waqf funds collected by the Penang Islamic Religious Council (PIRC) shows inconsistent amounts throughout the year, high and low according to different years. To overcome this problem, the PIRC has made some reforms such as cash waqf through salary deduction and providing online payment facilities, but these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…A study by (Zain, et al, 2019) also found that prudence of cash waqf significantly affected cash waqf intentions. In Penang, Malaysia, it was demonstrated that factors which influenced the intention to donate cash waqf were ukhuwah (Ukhuwwah is characterized as a fraternity or a connection between individuals), rewards, religious obedience, and awareness of cash waqf (Mokthar, 2018). Awareness also affected the intention to do cash waqf, while promotion of cash waqf did not influence the intention to perform cash waqf (Iqbal, et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by (Zain, et al, 2019) also found that prudence of cash waqf significantly affected cash waqf intentions. In Penang, Malaysia, it was demonstrated that factors which influenced the intention to donate cash waqf were ukhuwah (Ukhuwwah is characterized as a fraternity or a connection between individuals), rewards, religious obedience, and awareness of cash waqf (Mokthar, 2018). Awareness also affected the intention to do cash waqf, while promotion of cash waqf did not influence the intention to perform cash waqf (Iqbal, et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…rather than productive ones. Waqf does not have to be confined to land, buildings, or immovable property; it can also be in the form of finances or moveable goods (Mokthar, 2018). Since the National Shariah Board, Indonesia Ulama Council (DSN-MUI) issued a fatwa on cash waqf in 2012, and cash waqf has become well-known in Indonesia (Tanjung, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Mokthar (2018) investigated variables affecting Muslims in Penang's inclination to perform monetary waqf. A total of 395 Penang cash waqf donors provided the data, which were then statistically examined using descriptive statistical analysis utilizing the statistical program for social sciences (SPSS).…”
Section: Previous Studiesmentioning
confidence: 99%
“…The decision has dismissed any hesitation regarding cash waqf. Cash waqf has been implemented in several states in Malaysia which are Penang, Selangor, Pahang, Melaka, Perak and Terengganu (Mokthar, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%